COMPARATIVE CLINICAL AND AUDIOLOGICAL CHARACTERISTICS OF THE AUDITORY ANALYZER CONDITION IN PATIENTS WITH CHRONIC TUBOTYMPANIC OTITIS MEDIA - Grynko І.І.; Borysenko, O.M. (World of Medicine and Biology, 2017)
At a frequency of 8.0 kHz in patients with a teflon tube (T/tvt) - the magnitude of this indicator increases in the first 3 months after surgical intervention, and then gradually decreases after 6 and 12 months after the operation, and in patients with a silicone tube (T/svt) - practically does not change during all time after surgical intervention. The dynamics of thresholds for the perception of bone-carved sounds at different frequencies in patients with T/tvt after surgery is in most cases of a multi-directional nature. In patients with T/svt, the perception of bone-carved sounds at a frequency of 4.0 and 8.0 kHz increases in the first 3 months after surgical intervention, with subsequent preservation of its level until the 12th month after surgery. The dynamics of bone-air intervals at frequencies of 0.5 and 1.0 kHz in virtually all groups of patients with CTOM (except for T/tvt at a frequency of 1.0 kHz) after surgery has a similar nature - a gradual decrease with an increase in time after surgery (3 – 6 – 12 months), and the most pronounced decrease is observed in the first 3 months. At the frequency of 2.0 and 4.0 kHz, in most groups of patients with CTOM, the most pronounced reduction of bone-air intervals is noted not only after 3 months, but also in the interval from the 3rd to the 6th month. At a frequency of 8.0 kHz, the gradual decrease in the value of bone-air intervals with the increase in time after surgery is observed in the group of patients with T/svt, in patients with T/tvt its magnitude increases after 3 months after surgery, and in the interval between the 3rd and in the 6th months it decreases and then practically does not change.